Women’s Rights in the People’s Republic of China: Patriarchal Wine Poured from a Socialist Bottle - Chen, Leo K. (Columbia Journal of Asian Law, 1994)
The government of the People’s Republic of China (the “PRC”) and the Chinese Communist Party (the “CCP”) are rightfully proud of the improvements to women’s lives that have occurred under their leadership. Women’s feet are no longer bound, women are no longer legally purchased as slaves and concubines, women’s literacy has increased dramatically, and women now participate in practically all spheres of business, industry and government. Nonetheless, there is extensive evidence presented in the Chinese press and scholarly literature that the PRC remains a patriarchal,’ patrilineal and patrilocal society in which inequality based on sex2 persists. Equally disturbing are the serious doubts raised by many observers about the government’s commitment to the elimination of these problems and to the enforcement of women’s rights.3 They note that the situation of many women is quite shocking; women are routinely and illegally purchased and sold in open markets, forced into unwanted marriages, and suffer from disproportionately high rates of unemployment and illiteracy.